An in vitro Assessment of the Haemodynamic Features Occurring Within the True and False Lumens Separated by a Dissection Flap for a Patient-Specific Type B Aortic Dissection - Morris, Liam; Tierney, Paul; Hynes, Niamh; Sultan, Sherif (Frontiers in Cardiovascular Medicine, 2022)
One of the highest mortality rates of cardiovascular diseases are aortic dissections with challenging treatment options. Currently little work has been conducted in developing in-vitro patient-specific Type B aortic dissection models, which mimic physiological flow conditions along the true and false lumens separated by a dissection flap with multiple entry and exit tears. A patient-specific Stanford Type B aortic dissection scan was replicated by an in house manufactured automatic injection moulding system and a novel modelling technique for creating the ascending aorta, aortic arch and descending aorta incorporating arterial branching, the true/false lumens and dissection flap with entry and exit intimal tears. The physiological flowrates and pressure values were monitored, which identified jet stream fluid flows entering and exiting the dissection tears. Pressure in the aorta’s true lumen region was controlled at 125/85 mmHg for systolic and diastolic values. Pressure values were obtained in 8 sections along the false lumen using a pressure transducer. The true lumen systolic pressure varied from 122 mmHg to 128 mmHg along the length. Flow patterns was monitored by ultrasound along 12 sections. Detailed images obtained from the ultrasound transducer probe showed varied flow patterns with one or multiple jet steam vortices along the aorta model. The dissection flap movement was assessed at four sections of the patient-specific aorta model. The displacement values of the flap varied from 0.5 mm to 3 mm along the model. This model provides an unique insight into aortic dissection flow patterns and pressure distributions. This dissection phantom model can be used to assess various treatment options based on surgical, endovascular or hybrid techniques.